Design, synthesis, and biochemical evaluation of guanidine-based derivatives targeting protein kinases - Mihigo, Helene Bikorimana (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2022)
Kinases are some of the most intensively pursued classes of drug targets with approximately 243 distinct kinase inhibitors making it to human trials and most of these compounds are being investigated for the treatment of cancer. However, it has been found that deregulation of kinase function is also implicated in other disorders, including immunological, neurological, metabolic, and infectious diseases. Hence, development of small-molecule kinase inhibitors for the treatment of health disorders is still a medical unmet need. During the last 12 years Rozas? group has developed a series of guanidine-based compounds that inhibit the MAPK pathway. The first series of compounds studied, which have structural similarities to commercial protein kinase inhibitor Sorafenib, were found to inhibit the kinase B-Raf at an allosteric site. Subsequent series of derivatives were synthesised and biochemically tested, finding that these exert anticancer activity by means of a different mode of action, i.e. they do not inhibitor B-Raf. Further biochemical studies performed by our collaborators in the TBSI (Prof. D. Zisterer, School of Biochemistry and Immunology, TCD) indicate that the possible target is the STAT3/JAK2 pathway. Throughout the present project new guanidine-based derivatives will be synthesized pursuing two different objectives. On the one hand, in a structure-based drug design strategy, derivatives of the first lead compound will be computationally studied in an in-house model of ATP-containing B-Raf, and other B-Raf crystal structures. On the other hand, in a ligand-based drug design strategy new derivatives will be prepared to further confirm the target of the second series of compounds previously prepared and together with those will be evaluated in cell lines with active STAT3/JAK2; furthermore, computational studies will be carried out to confirm that the new lead and its derivatives cannot allosterically inhibit B-Raf, but it can inhibit protein kinase involved in the STAT3/JAK2 pathway.
APPROVED
Keywords: Cancer; Drug design; kinase inhibitors; Guanidine derivatives